Antifungal Activity of Coumarin Mammeisin Isolated from Species of the Kielmeyera Genre (Family: Clusiaceae or Guttiferae) - Helcio Cassemiro Marcondes; Tânia T. de Oliveira; Jason G. Taylor; Moisés Hamoy; Arman do Leonel Neto; Vanessa Joia de Mello; Tanus J. Nagem (Journal of Chemistry)
Coumarin mammeisin isolated from Kielmeyera elata was evaluated for its toxicity and antifungal activities. The toxicity of mammeisin was investigated by utilizing the Artemia salina methodology to determine its LD50 value. The minimum inhibitory concentration (MIC) of fungi Candida sp. was assessed for mammeisin, presenting equivalent activity to ketoconazole but displaying better results than fluconazole.